The impact of government policies on land use in northern Vietnam: an institutional approach for understanding farmer decisions - Clement, Floriane; Amezaga, Jaime M.; Orange, Didier; Tran Duc Toan (International Water Management Institute, 2007)
This report identifies the driving forces for reforestation in three villages of Northern Vietnam. Using an institutional analysis focused on the rules governing upland access and use, the authors assess the relative impact of state policies (reforestation programs and forestland allocation) on land use change. Findings show that the latter are indirectly responsible for reforestation, but not because of the incentives they provided. Instead, they disrupted the local rules governing annual crop cultivation and grazing activities leading to the end of annual cropping. Tree plantation was chosen by farmers as a last resort option. Lessons learned highlight the importance of local level studies and collective rules for land management.